Elevated Serum Lactate in Glioma Patients: Associated Factors - Sitter, Beathe; Forsmark, Annamaria; Solheim, Ole (Frontiers in Oncology, 2022)
IIntroduction: Serum lactate levels in brain cancer patients correlate with tumour malignancy grading, and serum lactate has been suggested as a potential biomarker and prognostic factor. The purpose of this study was to identify potential sources of elevated serum lactate in patients with brain gliomas by examining factors of importance for serum lactate production and clearance. Methods: In this cross-sectional study, data was collected from 261 glioma patients who underwent surgery from March 2011 to June 2015. We recorded patient gender, age, blood serum measures of lactate, glucose, pH, haemoglobin and base excess, patient health status, medications, and tumour characteristics. Patients with elevated and normal serum lactate levels were compared, and we explored if there were correlations between the variables. The association of serum lactate to the measured variables was investigated by simple and multivariable linear regression models. Results and Discussion: Patients with elevated serum lactate had higher blood glucose, larger tumour volumes, more tumour oedema, more often needed pressor medication during surgery, and more often received corticosteroid treatment. The investigated variables were highly correlated. Multivariable linear regression indicated that gender, tumour volume, Charlson Comorbidity index, hyperglycemia and corticosteroid treatment were associated with serum lactate levels. Histopathology was not an independent factor. In conclusion, comorbidities, hyperglycaemia and pre-surgical corticosteroid treatment exhibited the strongest association with serum lactate in glioma patients.